Is higher power shorter duration radiofrequency energy is better than lower power longer duration strategy in catheter ablation of atrial fibrillation A meta-analysis. (25th November 2020) - Khanra, D; Aggarwal, P; Kumar, H; Mishra, V; Jain, B; Reddy, K.K
Abstract: Background: An ideal strategy for radiofrequency ablation (RFA) of atrial fibrillation (AF) in the left atrium should be efficient enough to achieve transmural lesions in left atrium with no or minimal collateral tissue damage. Resistive heating of high power short duration (HPSD) RFA has been found to result in lesions larger in width but lesser in depth compared to lower power longer duration (LPLD) RFA in some experimental studies. Purpose: This meta-analysis was performed to compare procedural, short-term and long-term outcomes of HPSD versus LPLD RFA of AF. Methods: PubMed, Embase and Cochrane databases were systematically reviewed. Five observational studies meeting criteria were included in the meta-analysis. All the studies scored six or more points in the New-castle Ottawa scale. There were considerable variations in the ablation strategies across the studies. However, radiofrequency power more than 40W was considered as high power. Hypergeometric model with exact likelihood function was utilized for statistical analysis. Results: Baseline parameters and ablation details have been depicted in Table 1. 740 patients with HPSD and 287 patients with LPLD ablation strategies, were followed up from 6 to 30 months. Total procedural time (P value <0.0001) and ablation time (P value <0.0001) were significantly lower in the HPSD group than LPLD group. However, the fluoroscopy time was similar (P value = 0.09) in both the groups (Table 2). There were no occurrences of atrio-esophageal fistula or pulmonary venous stenosis in any of the studies. Cardiac tamponade (P value = 0.56), stroke (P value = 0.70) and AF recurrences (P value = 0.81), were similar in both groups (Table 2). Conclusion: Newer HPSD and conventional LPLD RFA, both the strategies are very safe procedure for treatment of RFA with low to no procedural complications. AF recurrence rates were reasonably high irrespective of ablation strategies, however, no strategy scored statistically better over the other one. Large randomized multi-centric studies with long-term follow up are needed to test the theoretical advantage of HPSD ablation over the traditional ablation strategy of AF. Funding Acknowledgement: Type of funding source: None